2020
DOI: 10.4103/aja.aja_77_19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and oncologic findings of extraprostatic extension on needle biopsy in de novo metastatic prostate cancer

Abstract: This study aimed to explore the clinical and oncologic findings in patients with de novo metastatic prostate cancer (mPCa) and extraprostatic extension (EPE) on biopsy. We retrospectively evaluated data on 630 patients with de novo mPCa between January 2009 and December 2017 in the West China Hospital (Chengdu, China), including evaluating the relationships between EPE and other variables and the association of EPE with survival outcomes by the Chi-square test, Kaplan–Meier curves, and the Cox proportional-haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thirty‐three of these studies correlated the presence of neuroendocrine staining to patient outcomes such as biochemical recurrence, clinical progression, overall survival and prostate cancer‐specific survival. The characteristics of the included studies are summarized in Table 1 [19–80] and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐three of these studies correlated the presence of neuroendocrine staining to patient outcomes such as biochemical recurrence, clinical progression, overall survival and prostate cancer‐specific survival. The characteristics of the included studies are summarized in Table 1 [19–80] and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, among the 12 RP specimens, eight (66.7%) showed multi-EPE locations that indicated extensive non-focal EPE, which was consistent with the higher non-focal EPE rate of 88% in a previous study by Fleshner et al [ 5 ]. Recently, Tolonen et al [ 26 ] and Chen et al [ 27 ] reported a higher biopsy incidence of EPE (4.9% [33/670] and 6.7% [117/1742], respectively) in their studies. Compared with our current study, the study cohort included a significantly higher percentage of patients with distant metastases (45.5% (15/33) and 59.8% (70/117), respectively), but much lower (12.5% (5/40)) in our cohort.…”
Section: Discussionmentioning
confidence: 99%